Potential reconstruction for a class of hyperbolic systems from incomplete measurements. (12th June 2018) - Carreño, Nicolás; Morales, Roberto; Osses, Axel
Abstract: In this article, we study the reconstruction of spatially dependent potentials in n coupled hyperbolic equations in cascade from n   −  1 components of the solution of the system. More precisely, we prove local uniqueness and Lipschitz stability for this inverse problem. The main tool is a Carleman estimate for a cascade system with missing observations.